Weak Type Estimates of Variable Kernel Fractional Integral and Their Commutators on Variable Exponent Morrey Spaces. (27th June 2019) - Shao, Xukui; Tao, Shuangping
Abstract : In this paper, the authors obtain the boundedness of the fractional integral operators with variable kernels on the variable exponent weak Morrey spaces based on the results of Lebesgue space with variable exponent as the infimum of exponent functionp ( · ) equals 1. The corresponding commutators generated by BMO and Lipschitz functions are considered, respectively.